PENGARUH PROFESIONALISME, KECERDASAN INTELEKTUAL DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS KERJA PEGAWAI DI BALAI DIKLAT PUPR WILAYAH I MEDAN - Adi Kuncoro; Malik Assalih Harahap; Yanjahuddin .; Muhammad Asrin Batubara; Heni Marito Harahap Marito Harahap (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of the problem in this study is whether there is an effect of professionalism on employee work effectiveness. Is there an effect of intellectual intelligence on employee work effectiveness. Is there an influence of organizational culture on employee work effectiveness. Is there any influence of professionalism, intellectual intelligence and organizational culture on the work effectiveness of the employees of the PUPR Region I Medan Training Center. The purpose of this study was to determine and analyze the effect of professionalism on employee work effectiveness. The influence of intellectual intelligence on employee work effectiveness. The influence of organizational culture on employee work effectiveness. The influence of professionalism, intellectual intelligence and organizational culture on the work effectiveness of the employees of the PUPR Region I Medan Training Center. The sample in this study amounted to 53 people. The data analysis technique used in this research is descriptive analysis and multiple linear regression analysis. The results of this study explain that the intellectual intelligence variable has a positive and significant effect on employee work effectiveness. Professionalism and organizational culture variables do not have a positive and significant effect on employee work effectiveness. The variables of professionalism, intellectual intelligence and organizational culture have a positive and significant effect on the work effectiveness of the employees of the PUPR Region I Medan Training Center.